Cooperative bridges: the role of risk perception in construction of resilient communities - Monno, Valeria; Frisullo, Daniela (AESOP, 2019)
This paper discusses the necessity to develop approaches to urban and regional planning and management for climate proof and resilient cities that incorporate the perception of risk associated with climate change. Our paper advocates for seeing community resilience as a process of social learning and highlights how risk perception could play a key role in it, which is crucial for envisioning and learning collectively how to produce more just and resilient socio-ecological urban and regional systems. Public risk perception is usually thought to have overriding importance in community resilience as it plays an important role in shaping community preparedness to risks. Our paper argues that in order to play a relevant role in constructing cities that are resilient to climate change, risk perception should be considered as a socio-cultural construction that embodies citizens’ experience of risk and its associated tensions between frames of crises and frames of change. Through a case study we show how the use of the categories that describe the tensions between the frames of crisis and change can be decisive in the constitution of resilient cities and spaces of learning. We call these categories cooperative bridges and discuss their role in building community resilience.
Keywords: community resilience; risk perception; planning and management of risks; floods